2012
DOI: 10.2478/v10184-011-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Centric diatoms of large rivers and tributaries in Hungary: morphology and biogeographic distribution

Abstract: Centric diatoms of 107 different Hungarian running waters were investigated. Among them the largest was the River Danube, from which more than one hundred plankton samples were analysed by scanning electron microscopy (SEM). Only one sample was analysed from creeks, which were the smallest running waters analysed in this study. There were also channels with slow currents flowing out of rivers or connecting different rivers. In total, 41 centric taxa belonging to 11 genera were found during this study. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 66 publications
4
60
0
10
Order By: Relevance
“…Scanning electron microscopy was performed with a FEG Tescan MIRA3 (TESCAN, Czech Republic). Diatom species identification followed Krammer & Lange-Bertalot (1991), Håkansson (2002), Houk et al (2010), Kiss et al (2012), and Cvetkoska et al (2014). Chrysophyte and dinoflagellate species identification followed Huber-Pestalozzi (1941), Taylor (1987), Popovský & Pfiester (1990), John et al (2002John et al ( , 2011 and Hansen & Flaim (2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scanning electron microscopy was performed with a FEG Tescan MIRA3 (TESCAN, Czech Republic). Diatom species identification followed Krammer & Lange-Bertalot (1991), Håkansson (2002), Houk et al (2010), Kiss et al (2012), and Cvetkoska et al (2014). Chrysophyte and dinoflagellate species identification followed Huber-Pestalozzi (1941), Taylor (1987), Popovský & Pfiester (1990), John et al (2002John et al ( , 2011 and Hansen & Flaim (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Although it had a very rare occurrence in Lake Visovačko during this study, it has been increasingly reported in the last decades from both lacustrine and riverine systems with different halobity, presumably as result of increased eutrophication, and is considered a potentially invasive species (Kaštovský et al, 2010;Abonyi et al, 2012;Kiss et al, 2012).…”
Section: Assemblage Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Europe: Germany (Hasle 1977, Kiss et al 1990, Ludwig and Schnittler 1996, Täuscher 2014, Hungary (Kiss et al 1990, Kiss et al 2012, France (Kiss et al 1990), Britain (Belcher and Swale 1979, Hartley et al 1986, Hartley et al 1996, Whitton et al 2003, Russia (Kiss et al 1990, Genkal 1992 (Europe) (Aysel 2005), Czech Republic (Kiss et al 1990, Kaštovský et al 2010, Netherlands (Dijkman and Kromkamp 2007), Albania (Kupe et al 2010), Macedonia (Levkov and Williams 2012), Spain (Pérez et al 2009), Romania (Caraus 2002, Caraus 2012). (Fig.…”
Section: Distributionmentioning
confidence: 99%
“…This concept is not restricted to the Tisza river catchment, but can be applied to other river systems (STANKOVIĆ et al 2012, ABONYI et al 2014. In middle and low discharge periods in the lower sections of alluvial rivers high biomass phytoplankton assemblages might develop, dominated mostly by chlorococcaleans and centric diatoms (SCHMIDT 1994, KISS and GENKAL 1996, KISS and SCHMIDT 1998, VÁR-BÍRÓ et al 2007, KISS et al 2012). It has been also shown that concerning the dominant algae, the phytoplankton of large potamal rivers is similar to that of shallow turbid lakes (REYNOLDS et al 1994).…”
Section: Introductionmentioning
confidence: 99%